Bedroom in the Douglas Boyle home at 3010 Country Club Road, 1958. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 4-13-58. Special section.
Bedroom in the Douglas Boyle home at 3010 Country Club Road, 1958.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth